Dictionary Ecology / Michael Allaby - Allaby, Michael (New York (State) / Oxford University press, 1998)
The updated second edition of the Dictionary of Ecology is the most comprehensive and authoritative dictionary of ecology available. Written in a clear, accessible style, it contains more than 6,000 entries on all aspects of ecology and related environmental scientific disciplines such as biogeography, genetics, soil science, geomorphology, atmospheric science, and oceanography
dicctionary of Ecolog
Col. Ref
Keywords: 1. ESTIMATES OF POPULATIONPARAMETERS 2. GEOLOGIC TIME -SCALE